THE STUDY OF USING SUGAR PAlM LEAVES (Arengapinnata) ASAIDS FORESCORT THE FISH ON CASHING NET IN KUOK VILLAGE KAMPAR REGENCY - BadrilIlham BadrilIlham; Syaifuddin Syaifuddin; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT    This research did on August 2018 in dry season in Kampar river Kuok village Kampar Regency. This research goal is to know the effect of using sugar palm leavesas escort toward haul so it can give the Information to development and modifications toward aids for escort fish. Method that used is survey with direct observation and involved in process of making aids. As for the haul with using aids with sugar palm leaves is Tinfoil Burb (Barbados schwanafeldii) with 47,9 kg (164 fishes), meanwhile the haul when do not use the aids with sugar palm leaves is Nile Tilapian(OreocromisNiloticus) 3,16 ( 13 fishes), Ray-finned (ThynnichtysPolulepis) 0,35 kg (7 fishes). Based on the haul can conclude that using the aids with sugar palm leaves as cashing net can be use, because the haul is much that do not use it.Key word:Sugar palm leaves, escort fish, cashing net, tinfoil burb.